Faktor yang Mempengaruhi Niat Pembelian Ulang Tiket Pesawat - Juliater Simarmata; Siska Amonalisa Silalahi; Marthaleina Ruminda (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2020)
This research aims to determine the effect of a service delay, firm reputation, and flight schedule availability on the intention to repurchase airline tickets. Data collection using questionnaires distributed to 100 Lion Air passengers who departed from Soekarno Hatta Airport with the aim of Medan, Padang, Palembang, Surabaya, Semarang, Yogyakarta, Bali, Ujung Pandang, Manado, Ambon, and Jaya Pura. Data analysis uses multiple linear regression. All data collected is declared valid and reliable and fits the requirements of the goodness of multiple linear regression. As a result, service delay, firm reputation, and availability of flight schedules have a partial and simulated effect on the intention to repurchase Lion Air tickets. Service delay, firm reputation, and availability of flight schedules contributed to the formation of 78.9% Lion Air ticket repurchase intentions. Schedule availability is the dominant variable in shaping the intention to repurchase Lion Air tickets.